E-learning / e-teaching of statistics: Students' and teachers' views - Wolfgang Härdle; Bernd Rönz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
Travel arrangements and flight ticket booking via inter-net is widely used nowadays and follow already certain standards. Although increasing activity for multimedia/web education components can be observed, we are far away from standards in this important area. Statistics can possibly profit the most from e-learning since it requires a variety of skills including handling of quantitative data, graphical insights as well as mathematical ability. In this paper we take two positions - the student's view and the teacher's view - and discuss their relative coherence in order to propose standards for e-learning of statistics. The proposed standards are flexible with regard to content, multi-functionality, interactive capability and design. For this reason the main focus may be directed on quality of e-learning tools in order to meet both teacher's and student's requirements. This is especially true for statistics which is taught in various disciplines. We present our thoughts and exemplify them via the e-learning/e-teaching tools MM*Stat and e-stat. The struc-ture and the main characteristics of both multimedia tools will be explained. Then it will be described how such standards may be transferred to other cultures, languages or disciplines via the platform MD*Book.
urn:nbn:de:kobv:11-10049605
Keywords: 330